Application of virtual windows to determine the path of a uniformly moving obstacle - Mohd. Uzir Kamaluddin; Hj. M.A. Hj. Mansor (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Two virtual windows are used to determine the path of a single uniformly moving obstacle. If the path of the obstacle crosses the two virtual windows, then its path can be easily determined. A simulation is implemented to ascertain the viability and accuracy of this technique.